Dietary Patterns and Weight Status of Primary School Children in Serbia - Bozic, Predrag; Djordjic, Visnja; Markovic, Lidija; Cvejic, Dragan; Trajkovic, Nebojsa; Halasi, Sabolc; Ostojic, Sergej (Frontiers in Public Health, 2021)
The purpose of the present cross-sectional study was to examine dietary patterns and the prevalence of underweight, overweight, and obesity among Serbian children. Furthermore, the study analyzed the association between dietary patterns and weight status. A nationally representative sample of 6–9-year-old children (n = 3,067) was evaluated as part of the Fifth Round World Health Organization European Childhood Obesity Surveillance Initiative. The children's height and weight were measured by trained field examiners, while their parents or guardians filled paper versions of the food frequency questionnaire to collect information related to the child's breakfast habits and food and beverage intake. According to the International Obesity Task Force cut-off points, the overall prevalence of overweight (including obesity) and underweight were 28.9 and 8.1%, respectively. The majority of parents reported that their children (84.5%) had breakfast every day, while only 39.5 and 37% of children had daily fruit and vegetable consumption, respectively. The children who do not eat breakfast every day are more likely to be obese (OR = 1.50), while a higher intake frequency of nutrient-poor beverages such as soft drinks increases the risk of being not only overweight (OR = 1.32) but also underweight (OR = 1.39). Regular monitoring and understanding of dietary patterns and weight status is crucial to inform, design, and implement strategies to reduce national and global diet and obesity-related diseases. Urgent actions need to be taken from public policymakers to stop and reverse the increasing trend of overweight (including obesity) among Serbian children.